Relationship Between Food Security Status in a Caregiver's Family of Origin and Current Feeding Practices Among Low-Income, Single, Female Primary Caregivers. Issue 4 (October 2022) - Lappan, Sara N.; Harman, Tara; Pavela, Greg; Hendricks, Peter
Abstract : A child's familial environment is paramount to the formation and maintenance of their health behaviors. Factors that influence a child's health behaviors include parental modeling, types of available food, timing of food availability, and characteristics of the home environment. Previous research has demonstrated an association between a caregiver's current food security status and feeding practices, but no studies have explored the association between food security in the caregiver's childhood and their current feeding practices. This study investigates the relationship between parental food insecurity (both current and childhood) and child feeding practices. The US Household Food Security Survey and the Child Feeding Questionnaire were completed by 103 low-income, single, female primary caregivers. Results indicated that caregivers who reported current food insecurity expressed greater tendency to pressure their children to eat. Caregivers who reported food insecurity during their childhood also expressed greater tendency to pressure their children to eat and a greater concern about their child's weight. These findings can serve in both research and clinical efforts as an early screening tool to indicate families most in need of accessible resources. Findings also help to highlight the transgenerational nature of food insecurity, including its residual effects on health behaviors.